Konsep Kewenangan Bawaslu Kabupaten Sleman Pada Putusan Ultra Petita Adjudikasi Pemilu Tahun 2019 - Lis Budi Qurnianti; B. Hestu C. Handoyo; E. Sundari (Sekolah Tinggi Ilmu Hukum Prof Gayus Lumbuun, 2025)
This research is entitled “The Concept of Bawaslu Sleman Regency’s Authority in the Ultra Petita Decision of the 2019 Election Adjudication.” It addresses two main legal issues: (1) Whether the ultra petita decision issued by Bawaslu Sleman Regency in the adjudication of the 2019 legislative candidacy administrative dispute for the Sleman Regency Regional People's Representative Council (DPRD) is legally justifiable; and (2) How Bawaslu Sleman Regency’s authority in issuing an ultra petita decision can be viewed from the perspective of legal certainty theory. This research employs a normative legal method. Data were collected through literature review and interviews with several informants. The findings reveal that Bawaslu Sleman Regency's ultra petita decision is legally justifiable, as it was based on fulfilling the constitutional rights of legislative candidates from the Hanura Party in Sleman Regency, in accordance with Article 28J of the 1945 Constitution. From the perspective of legal certainty theory, Bawaslu’s authority in issuing such a decision aligns with Gustav Radbruch’s concept of legal certainty, which he defines as Sicherheit durch das Recht or certainty through law.